Biliary stricture due to a migrated suture after laparoscopic distal gastrectomy. Issue 4 (20th February 2018) - Noji, Takehiro; Kurashima, Yo; Nakanishi, Yoshitsugu; Asano, Toshimichi; Ebihara, Yuma; Nakamura, Toru; Murakami, Soichi; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Mitsuhashi, Tomoko; Hirano, Satoshi
Abstract: Benign biliary strictures have a broad spectrum of etiologies. There have been no reported cases, however, of a biliary stricture secondary to a migrated suture after laparoscopic distal gastrectomy (LDG). Here, we report one such case. The patient was a 60‐year‐old man who underwent LDG with Roux‐en‐Y reconstruction for early gastric cancer. Pathology revealed early cancer (T1N0M0) with a curative resection. Two years after LDG, the patient was found to have elevated hepatobiliary enzymes. After further workup, the new diagnosis was invasive cholangiocarcinoma (T2N0M0), and the patient underwent pancreaticoduodenectomy. Intraoperatively, a monofilament nylon suture was found in the center of a biliary stricture; this suture was previously used for duodenal closure during LDG. Histologically, the bile duct with stricture showed chronic inflammation and fibrosis. Despite no evidence of invasive carcinoma on pathology, a small lesion of adenocarcinoma in situ was found in the superior common hepatic duct.